The Influence of Corporate Governance Mechanisms on Financial Performance. Is Gender Diversity a Relevant Board Characteristic? - Raluca Andreea Achima; Camelia Iuliana Lungu (Journal of Accounting and Management Information Systems (JAMIS), 2025)
Research Questions- To what extent is the financial performance of Romanian listed companies influenced by corporate governance mechanisms? Does a higher proportion of women on boards of directors lead to better financial performance in listed companies? Motivation- As a consequence of the corporate scandals occurred on a global scale, numerous developed countries have implemented initiatives to improve governance mechanisms towards maintaining financial stability. For emerging countries, the companies are still struggling to identify and address management shortcomings in ensuring financial performance. In the light of these developments, research on the impact of board characteristics on financial performance in case of emerging countries are still generating interesting results. Idea- The purpose of this study is to present empirical evidence of the relationship between board characteristics and financial performance for companies listed on an emerging stock exchange. In addition, it discusses whether gender diversity is a relevant corporate governance mechanism that may influence the financial performance. Data- The data were collected from the annual reports of companies listed on the Bucharest Stock Exchange for the period 2020-2023. Tools- Regression analysis was applied to examine four research hypotheses addressing the impact of various board characteristics on corporate financial performance. Robustness tests were applied to validate the results. Findings- The results reveal that CEO duality and board size positively influence both ROA and ROE, while board independence exerts a negative but not significant influence on both performance indicators. Contrary to results of studies conducted on developed countries, this research indicates that the proportion of women on the board of directors has a statistically significant negative impact on the financial performance of Romanian listed companies. Contribution- This paper provides up-to-date evidence for the Romanian companies, on the influence of corporate governance mechanisms on financial performance and the relevance of board gender diversity. It offers researchers, regulators, and investors, valuable insights, that may be used to enhance financial performance and mitigate corporate failures, for an emerging country.
Keywords: M41; G34; 650; corporate governance mechanisms; board characteristics; financial performance; gender diversity; Bucharest Stock Exchange